Ant recolonization of rehabilitated bauxite mines at Trombetas, Pará, Brazil. - Majer, Jonathan (1996)
Ant species were sampled in three rainforest and 10 rehabilitated bauxite mine plots at Trombetas, in the tropical monsoonal region of Brazil. Rehabilitation ranged from 0 to II years in age and was mainly performed by planting mixed native forest tree species. One plot supported single-species blocks of Australian Eucalyptus and Acacia species. Two hundred and six ant species were recorded, of which 82 were exclusively found in the native vegetation, 54 were confined to the rehabilitation and 70 were found in both situations. In contrast with other studies, ant species richness in the Eucalyptus/Acacia plantation was as great as in the areas rehabilitated with native vegetation. The overall rate of return of ant species was considerably greater than in mines situated within subtropical regions of Brazil, Africa and Australia. However, if the greater richness of ants in the native vegetation at Trombetas was accounted for, the proportional return of the original ant fauna was not particularly rapid. The return of ant species slowed as the rehabilitated areas aged. In comparison with forest, the rehabilitation was characterized by proportionately more generalist species and fewer specialists, especially from the soil and litter layers. The full range of habitat requirements for the ant community has not been restored by the eleventh year of rehabilitation and further management may be required to enhance the degree of colonization. It is suggested that the findings for ants may apply to other components of the biota as well.